The decreasing effect of troxerutin on the level of pro-inflammatory cytokines in rats with sepsis caused by the experimental cecal puncture - Ali Shaker; Siamak Kazemi-Darabadi; Yaser Jafari-Khataylou (The Iranian Journal of Veterinary Science and Technology, 2021)
Sepsis is the main mortality factor in patients undergoing surgery and its treatment currently includes cardiac resuscitation and reducing the immediate risk of infection. Troxerutin is a common compound in vegetables, fruits, and seeds and has several biological activities, including anti-platelet, anti-serotonin, antioxidant, and anti-inflammatory effects. Accordingly, we hypothesized that it can decrease interleukin 1 (IL-1) and tumor necrosis factor-alpha (TNF-a) levels in the serum of rats with sepsis. Twenty-four adult male Sprague-Dawley rats were used in this study. The rats were equally and randomly divided into 3 groups: sham operation group, control group, and treatment group. Both the control and treatment groups underwent surgical cecal ligation and perforation. Troxerutin (130 mg/kg) was injected subcutaneously twice a day to the animals of the treatment group for 3 days or until the animals’ death. Surviving rats were euthanized after 1.5 ml of blood samples were taken 3 days after the cecal ligation and perforation. IL-1 and TNF-a were measured by the blood serum ELISA assay. The differences in mortality rates were significant between the control group and the other two groups (p = 0.008). The results showed a significant increase in IL-1 and TNF-a in the control group compared to the sham group (p < 0.05). In addition, the levels in the treatment group significantly decreased compared to the control group (p < 0.05). In conclusion, our results indicate that troxerutin could increase survival in rats developing septic shock by reducing pro-inflammatory cytokines including IL-1 and TNF-a.